A Comparative Study of Wasiat Wajibah in Indonesia, Egypt, and Pakistan from the Perspective of Maqashid al-Sharia - Tamimatun Nihayah; Abd Rouf (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
The wasiat wajibah is a form of reform in Islamic inheritance law that has evolved to provide protection to family members who do not receive their rights under the classical inheritance system. This study aims to analyze the regulations governing wasiat wajibah in Indonesia, Egypt, and Pakistan and to assess their relevance as an instrument of family protection from the perspective of the maqashid al-sharia. This study employs a normative legal method using legislative, conceptual, and comparative legal approaches. Legal materials were obtained from legislation, legal literature, and scholarly articles, which were analyzed qualitatively. The results indicate that all three countries share the same objective to provide economic protection to family members who may lose their rights due to the application of the classical inheritance system but employ different mechanisms. Indonesia regulates the mandatory bequest for adopted children and adoptive parents through Article 209 of the Compilation of Islamic Law; Egypt grants a mandatory bequest to grandchildren who are barred from receiving an inheritance through Qanun al-Wasiyyah No. 71 of 1946; while Pakistan implements a system of heir representation through Article 4 of the Muslim Family Laws Ordinance of 1961. From the perspective of maqashid al-sharia, these three models are oriented toward the protection of descendants (hifz al-nasl) and the protection of property (hifz al-mal), thereby demonstrating that Islamic inheritance law possesses the flexibility to achieve justice and the public interest in accordance with the needs of society.